2021
DOI: 10.1186/s13690-021-00647-8
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 PCR and antibody testing for an entire rural community: methods and feasibility of high-throughput testing procedures

Abstract: Background Early in the pandemic, inadequate SARS-CoV-2 testing limited understanding of transmission. Chief among barriers to large-scale testing was unknown feasibility, particularly in non-urban areas. Our objective was to report methods of high-volume, comprehensive SARS-CoV-2 testing, offering one model to augment disease surveillance in a rural community. Methods A community-university partnership created an operational site used to test most… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 5 publications
1
5
0
Order By: Relevance
“…This drive-through POST system at PUMS, which operated as a unified and efficient testing site accessible to both urban and rural populations, was a pioneering solution in Poland and an alternative to similar drivethrough models previously reported in the literature [6][7][8][9][10][11][12][13][14]. Additionally, according to the authors' knowledge, the current study is the first presentation of the experience of a drive-through point for screening and testing COVID-19 in Poland.…”
Section: Discussionmentioning
confidence: 83%
“…This drive-through POST system at PUMS, which operated as a unified and efficient testing site accessible to both urban and rural populations, was a pioneering solution in Poland and an alternative to similar drivethrough models previously reported in the literature [6][7][8][9][10][11][12][13][14]. Additionally, according to the authors' knowledge, the current study is the first presentation of the experience of a drive-through point for screening and testing COVID-19 in Poland.…”
Section: Discussionmentioning
confidence: 83%
“…In this study, we learned that the health professionals who came from other regions to support Yangzhou did not have a fixed working place, which led to constant changes in personnel. Some studies suggested that consistent staffing on all days helped to optimize proficiency and helped in cooperation [36], while some studies addressed it through interdisciplinary collaboration and active reinforcement programs implemented [37]. In-formation technology should be fully used in nucleic acid testing, and it was feasible to recruit volunteers and materials through the online news platform [38].…”
Section: Discussionmentioning
confidence: 99%
“…Four weeks after shelter-in-place health orders, we conducted active population-based surveillance for SARS-CoV-2 infection in Bolinas, California among residents over 4 years of age and in Marin County first responders and essential workers. In close partnership with the community and the Marin Department of Public Health, oropharyngeal and mid-turbinate swabs for reverse-transcription PCR (RT-PCR) testing and blood for antibody testing were collected over 5 days (April 20-April 24, 2020) as previously described in detail and summarized below [17].…”
Section: Methodsmentioning
confidence: 99%
“…These community leaders and stakeholders, together with the study leadership, participated in a virtual Town Hall the week before testing and week after results provision to introduce the study to the community, provide education, answer questions, and address concerns [17].…”
Section: Study Setting and Community Partnershipmentioning
confidence: 99%